DESAIN ALTERNATIF STRUKTUR ATAS JEMBATAN PEMBANGUNAN JALAN BEBAS HAMBATAN CISUMDAWU STA.0+630.300 - STA.0+692.200 MENGGUNAKAN SOFTWARE BRIDGE DESIGNER 2016 - Muhamad Syarifudin; Sutrisno . (Jurnal TEDC, 2022)
donesia is one of the countries with a large enough area and has a very large population in the world. The need for infrastructure for transportation is one of the main needs that must be provided by the government. One of the national transportation development is the construction of the Cileunyi – Sumedang – Dawuan Highway to be a solution for public transportation for our developing country. The length of this Highway track 60.47 kilometers through hills and plantations along the track, therefore the bridge becomes one of the options in this development, especially in Phase Three. The Steel Box Girder Bridge was selected as an Alternative Design case study by adding an Upper Strucktur using a steel frame to determine the strength of the bridge along the work point (Sta.0+630,300 – Sta.0+692,200) and ended with an animation-shaped test in Software Bridge Designer 2016. The research methods selected use developmental analysis and planning. The results of the animation study and test at Software Bridge Designer 2016 showed that the safe steel size used for Elongated Gelagar = CS Bar 500x500, Transverse Hashtag = CS Bar 500x500, Upper Rod Frame = CS Bar 300x300, Vertical Rod Frame = CS Bar 140x140, Diagonal Rod Frame = CS Bar 140x140, Yield Stress = 25000kN/m² and Mass Density = 7850 Kg/m³ on the bridge and costs to be spent at Rp. 19,423,893,00